The Correlation of Students’ Learning Styles, Learning Motivation, and Speaking Ability - Syafrizal Syafrizal; Nurhaedah Gailea; John Pahamzah; Yudi Juniardi; Ifrohatul Fauqoh Nikmah (English Education Department, Postgraduate, Universitas Sultan Ageng Tirtayasa, Indonesia, 2020)
The study aimed at finding out the correlation between (1) Students’ learning style in speaking ability of communication and broadcasting Islam major, (2) correlation of learning motivation in speaking ability of communication and broadcasting Islam major, (3) correlation of students’ learning style and learning motivation in speaking ability of communication and broadcasting Islam major. This study was carried out at Communication and broadcasting Islam Major in UIN Sultan Maulana Hasanuddin Banten. The method which is used in this study was the correlational method. The sample was 30 students which were taken by a simple random sampling technique. The instruments in collecting the data were questionnaires and tests. The questionnaire was used to collect the data on students’ learning styles and learning motivation. The technique which was used to analyze the data was Simple correlation and Multiple Regression Correlation which were computed by the Statistical Product and Service Solutions (SPSS). The results of the analysis of the data on this research show that: (1) there is a significant correlation between learning style and speaking ability ρ < α (0.043 < 0.05), (2) there is a significant correlation between learning motivation and speaking ability ρ < α (0.041 < 0.05), and (3) there is a significant correlation between learning style and learning motivation toward speaking ability ρ < α (0.045 < 0.05).